MESSAGE FROM THE ORGANISING COMMITTEE - Rátgéber, László (Sport- és Egészségtudományi füzetek, 2025)
Learning and inspiration - these are the key words. The discipline and the opportunity offered by such confer-ences are crucial for the future of a sport. Strategy develop-ment requires successful and highly educated profession-als. We should never be ashamed of learning new things. Whether a sentence, a word or just body language inspires the participants, it was already worth organizing the con-ference. In the summer, we will hold our 6th International Basketball Conference at the National Basketball Academy. These conferences are like six semesters of a master’s de-gree.